Effects of cold treatment on agricultural characteristics of garlic bulbs cv. Chonan. II. Physiological characteristics - Silva, José Luiz Oliveira da; Alvarenga, Marco Antonio Rezende (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried in the area of the "Departamento de Agricultura da Escola Superior de Agricultura de Lavras", MG, Brasil, from August 1980 to January 1981, in a Dark-Red dystrophic Latosol. Bulb, leaf, total dry weight and leaf area index, and dry matter production rate were determined. The experimental design used was a split plot in complete randomized blocks with four replications. The plots were the sampling periods and part of them were taken each ten days and split plots were three periods of cold treatment (10, 20 and 30 days) at 4°C and the check test. A precocity of 30 days for the treatments 20 and 30 days in the freezer was shown. The effect of the ten-days cold treatment did not show a great advantage in the plant development. The highest photosynthesis rate was observed at 50 days after planting, and the highest leaf development occurred between 80 and 90 days, showing a decrease up to 100 days for treatments 20 and 30 days in the freezer before planting.